2006
DOI: 10.4103/0019-5359.27220
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and hypocholesterolemic effect ofLactobacillus caseisspcasei(biodefensive properties of lactobacilli)

Abstract: BACKGROUND: A positive correlation between an individual's cholesterol level and development of CHD has been suggested. Low levels of high-density lipoprotein cholesterol (HDL-C) and high levels of low-density lipoprotein cholesterol (LDL-C) are important risk factors and oxidation of LDL has been implicated as an initiator of atherosclerosis. AIM: Attempts are being made worldwide for the search of effective antioxidants that can prevent oxidation of LDL. Role of fermented milk and culture containing dairy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 21 publications
3
38
0
3
Order By: Relevance
“…56 Several evidences showing some antioxidant properties of Lactobacilli were reported in literature. 59,60 The data obtained in this study showed that LAB induced a high significant decrease in lipid peroxidation in liver and kidney tissues as well as a decreasing in MDA production, proving that LAB presented effective antioxidative properties and could scavenge the excess of free radicals.…”
Section: Experimental Groupsmentioning
confidence: 55%
“…56 Several evidences showing some antioxidant properties of Lactobacilli were reported in literature. 59,60 The data obtained in this study showed that LAB induced a high significant decrease in lipid peroxidation in liver and kidney tissues as well as a decreasing in MDA production, proving that LAB presented effective antioxidative properties and could scavenge the excess of free radicals.…”
Section: Experimental Groupsmentioning
confidence: 55%
“…Analysing the results for ARP values in the group of the natural fermented milks one can conclude that there was lower diversity of the results (differences not statistically signifi cant, p > 0.05) when compared to FRAP values. The radical scavenging ability in this group was estimated in the range of 0.07-0.24 mM TE/kg, and the highest values were noticed for YN8 and YN9 yoghurts (both containing probiotic L. casei DN-114001 strain) and for the KN4 kefi r. Antioxidant activity of L. casei bacteria was confi rmed in both in vitro (Virtanen et al, 2007) and in vivo studies (Kapila and Sinha, 2006;Zhang et al, 2010). Moreover, the results obtained by Jain et al (2009) revealed that among three tested lactic acid bacteria (LAB) strains, the culture of L. casei was characterised by the highest ability to eliminate DPPH, hydrogen peroxide, malonaldialdehyde radicals, and to inhibit linoleic acid peroxidation.…”
Section: Strawberrymentioning
confidence: 66%
“…been shown that atherosclerosis could be suppressed by controlling the concentration of cholesterol in the serum (Kapila et al, 2009). Lower concentrations of cholesterol in yolk and blood in connection with probiotic strains supplementation have been described by Panda et al (2003), Kurtoglu et al (2004), Li et al (2006) and Salma et al (2007b).…”
Section: Discussionmentioning
confidence: 91%